The problems of work scientology applied to the workaday world - Hubbard, L. Ron (La Fayette Ron) 1911-1986 (Religious Technology Center L. Ron Hubbard Library, 2010)
Outlines the principles and laws of Scientology that apply to every endeavor, every problem of work.